Delineating the roles of Cr and Mo during ordering transformations in stoichiometric Ni2(Cr1−x, Mox) alloys. (1st September 2015) - Verma, A.; Singh, J.B.; Wanderka, N.; Chakravartty, J.K.
Graphical abstract: Abstract: Commercial NiCrMo based superalloys form ordered Ni2 (Cr,  Mo) precipitates at intermediate temperature, which deteriorates their mechanical and corrosion properties, and whose kinetics varies significantly with alloy compositions. The aim of the present study is to understand the roles of Cr and Mo solutes on ordering kinetics and transformation mechanisms in NiCrMo alloys. On the basis of the present study, it has been concluded that the Ni2 (Cr,  Mo) phase evolves with a sluggish ordering kinetics when its formation is governed only by the lattice diffusion of Cr, but its kinetics increases beyond a certain Mo/Cr ratio when lattice diffusion of Mo also starts contributing to its formation. This change has been found to occur in alloys having Mo/Cr ratio = 1 and has been attributed to partial change in the nature of atomic bonding from covalent type to metallic type. This change in the nature of bonding also reduced the necessary undercooling required below the disorder/order phase boundary for the precipitation of the ordered phase. Micromechanisms of ordering transformations involved in the evolution of the ordered phase have been described by a qualitative transformation model.